A seiva e o traço: configurações da memória na escrita do diário de viagem do botânico Francisco Freire Alemão (1859-1861) - Teixeira, Karoline Viana (2017)
This thesis deals with Francisco Freire Alemão’s travel journal. One of the leading Brazilian naturalists of the 19th century, Freire Alemão wrote this journal during the Scientific Exploration Commission, an expedition that ran between 1859 and 1861 in the backlands of Ceará, as well as parts of the provinces of Rio Grande do Norte, Piauí and Pernambuco. Freire Alemão accumulated the functions of president of the Scientific Commission and head of the Botanical Section, bringing to the Court a herd of 14,000 plants. Considered the first scientific trip composed exclusively by Brazilian naturalists, the Scientific Commission of Exploration reflected the effort of the Brazilian Empire in the promotion of discoveries that were to leverage the economy of the country, as it happened in the European nations and in the United States. Despite the criticism, scarcity of funds and administrative and personal disagreements that undermined the continuity of its work, I try to approach the experience of the Scientific Commission within the possibilities and limits in the use of science as the intellectual arm of the development of the Brazilian Empire. Because of the cessation of the work of the Botanical Section and the illness of Freire Alemão, the diary remained in its original form, without any type of editing or cut, an operation that would have happened if it had been published. My purpose is to highlight the writing of the diary as the production of a particular memory, through a writing produced from a strategic knowledge aimed not only for the flourishing of science, but also to meet the demands of a policy aimed at using all the potentiality of the natural world. But a writing that at the same time registers an experience permeated by uncertainties, misunderstandings, unusual body reactions to the environment and inversions of the role of observer and observed. As a record of a memory and memory of a record, I take the diary as a privileged object to approach lived experiences, as well as to discern the diverse and complex fabric of mnemonic compositions, bringing together the connections between the subject in his private experiences and his relation with the collective.